2018
DOI: 10.1364/oe.26.002708
|View full text |Cite
|
Sign up to set email alerts
|

In situ retrieval and correction of aberrations in moldless lenses using Fourier ptychography

Abstract: Liquid droplets cured at low temperatures or using ultraviolet light are primary approaches for fabricating refractive lenses without molds. Until now the performance of moldless lens fabrication process relied heavily on this step to precisely control the shape of each liquid droplet. Hence, a major hurdle in lenses fabricated from liquid droplets is the large variability of droplet shapes because they are sensitive to small amounts of interfacial forces. The shape of the final droplet critically affects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…4(c)] 15,80,[106][107][108][109][110][111] and the defocus of the sample 112,113 can be numerically corrected for, even under severe conditions. 94,114 Based on this principle, Chung et al 115 reported a Fourier ptychographic retinal imaging method that can correct for eye lens aberrations and thereby enable full-resolution imaging of the retina. Similarly, postacquisition digital refocusing can be used to extend the depth of field for imaging microfilters containing captured tumor cells, 97 96-well plate, 112 blood smear, 109 and pathological slides.…”
Section: Fourier Ptychographymentioning
confidence: 99%
“…4(c)] 15,80,[106][107][108][109][110][111] and the defocus of the sample 112,113 can be numerically corrected for, even under severe conditions. 94,114 Based on this principle, Chung et al 115 reported a Fourier ptychographic retinal imaging method that can correct for eye lens aberrations and thereby enable full-resolution imaging of the retina. Similarly, postacquisition digital refocusing can be used to extend the depth of field for imaging microfilters containing captured tumor cells, 97 96-well plate, 112 blood smear, 109 and pathological slides.…”
Section: Fourier Ptychographymentioning
confidence: 99%
“…Increased resolution/SBP Aperture synthesis [1,[21][22][23][24] Phase imaging Phase retrieval [25][26][27][28][29] Digital refocusing Phase retrieval [1,27,30] Aberration correction EPRY [24,[31][32][33] Long working distance low NA objective [34,35] Sub-λ imaging high-angle illumination [21][22][23]34,36,37] Multimodal imaging scanning illumination angle [24,34,38] High-speed LED & camera multiplexing [26,[39][40][41][42][43][44][45] Compact and portable Novel hardware [33,46,47] 3D imaging light field, 1st Born, multislice [48][49][50][51][52][53][54][55][56] computation using low numerical aperture (NA) op...…”
Section: Achieved By Referencesmentioning
confidence: 99%
“…[31] for measuring and correcting for aberrations within the coherent transfer function from a standard FP data set. This capability has since allowed FP to be implemented with extremely aberrated lenses, such as moldless lenses [47] and mobile phone camera lenses [33] as shown in Fig. 9.…”
Section: Aberration Recoverymentioning
confidence: 99%
“…In laser scanning microscopes (LSM), the optical SBP is calculated by dividing the field of view (FOV) over the lateral point spread function (PSF) in a two-dimensional raster scan [3,6]. Hence, low SBP is attributed to non-uniform distribution of spatial aberrations across the entire FOV arising from either optical imperfections of optical elements across the entire system (system aberrations (SA)), imperfections towards the edges of the imaging FOV of a standard imaging objective lens (lens aberrations (LA)) [5,7,8] and/or sample-derived refractive index inhomogeneity (sample aberrations (SAA)) [9,10]. While customized objectives or scan lenses have extended the imaging FOV [3,6,11] to increase their SBP, they account only for optical distortion, which stem from field curvature of the lens, but not distortion caused by the sample.…”
Section: Introductionmentioning
confidence: 99%